Effects of intercropping, home gardening, and agrisilviculture on soil physicochemical properties in Malaysia - Jacklin, Mathew; Mohamad Hilmi, Ibrahim (Springer Nature, 2026)
Agriculture is essential for human survival, but unsustainable practices threaten its longterm viability. Intensive agricultural activities such as tillage, residue burning, and agrochemical use can lead to soil erosion and degradation. Sustainable practices such as intercropping, agroforestry, and home gardening are known to improve soil health and reduce environmental impact. This study investigates the effects of these practices on selected soil properties in Siburan, Sarawak. Soil samples were collected from three sites representing intercropping, agrisilviculture, and home gardening at depths of 0–20 cm, 20–40 cm, and 40–60 cm. The samples were analysed for moisture content, bulk density, pH, organic matter, organic carbon, total acidity, and exchangeable aluminium and hydrogen ions according to the standard procedure. Results show that soil moisture content in home gardening (57.89%) is significantly higher (p <0.05) than in agrisilviculture (47.84%) and intercropping (25.60%). Organic matter content was also highest in-home gardening at 8.38%, while soil acidity and exchangeable aluminium were significantly elevated in home gardening soils compared to other practices. In contrast, the cations exchangeable capacity under home gardening is the lowest compared to agrisilviculture and intercropping. These findings emphasize the need to understand how different agricultural practices influence soil properties, providing practical insights for improving soil management strategies in Siburan, Sarawak.